2007
DOI: 10.1080/02664760701592125
|View full text |Cite
|
Sign up to set email alerts
|

Holt–Winters Forecasting: An Alternative Formulation Applied to UK Air Passenger Data

Abstract: This paper provides a formulation for the additive Holt-Winters forecasting procedure that simplifies both obtaining maximum likelihood estimates of all unknowns, smoothing parameters and initial conditions, and the computation of point forecasts and reliable predictive intervals. The stochastic component of the model is introduced by means of additive, uncorrelated, homoscedastic and Normal errors, and then the joint distribution of the data vector, a multivariate Normal distribution, is obtained.In the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 12 publications
(19 reference statements)
0
33
0
Order By: Relevance
“…The Holt-Winters model, also called the cubic exponential smoothing model, is one version of the exponential smoothing model. It is suitable for processing a single variable time series with seasonal factors and trends [22]. When the Holt-Winters model is used to predict the spare parts demand, the suitable smoothing parameters should be selected based on the demand of the historical spare parts according to the specific predict cycles.…”
Section: Analysis Of Alternative Prediction Modelsmentioning
confidence: 99%
“…The Holt-Winters model, also called the cubic exponential smoothing model, is one version of the exponential smoothing model. It is suitable for processing a single variable time series with seasonal factors and trends [22]. When the Holt-Winters model is used to predict the spare parts demand, the suitable smoothing parameters should be selected based on the demand of the historical spare parts according to the specific predict cycles.…”
Section: Analysis Of Alternative Prediction Modelsmentioning
confidence: 99%
“…Accurate estimates of initial conditions can result in better forecasting accuracy [1]. Recently, some researches have proposed maximum likelihood estimation for estimation of smoothing parameters and starting values [9,10], as well as other optimization methods [7,11,12]. In this research, new heuristic rules to estimate initial conditions for the Holt-Winters multiplicative method are introduced.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], Bermudez, et al state: "Forecasting competitions have reported the surprising forecasting accuracy of Holt-Winters methods which were obtained with minimal effort in computation and model identification." However, standard exponential smoothing methods are commonly fitted in two steps.…”
Section: Introductionmentioning
confidence: 99%
“…Bermudez, Segura and Vercher (2007) argued that the additive Holt-Winters model was inappropriate if the seasonal components or the error variance depend on the level of the series, but it could also be useful after an adequate data transformation for the UK air passenger data. In the study of Witt, Newbound and Watkins (1992) showed that the exponential smoothing generates method forecasts with lower error magnitudes than other modeling methods for Las Vegas arrivals data.…”
Section: Introductionmentioning
confidence: 99%